Dostop do zdravstvenih storitev in medicinskih stvari - Strban, Grega (Delavci in delodajalci, 2024)
Numerous political and legal documents emphasise the importance of access to high quality medical services and medicinal goods. They are important not only for ensuring existence and free development of every individual, but of society as such. To enable highest attainable standard of health a well-functioning public healthcare system is required. It should provide for all kinds of access to healthcare. Geographical access shall provide not only for proximity of a healthcare provider, but also its quality and safety. Timely access has to be evaluated individually and not administratively. Essential is also economic access, making healthcare affordable. Procedural access has to guarantee bodies and available procedures to enforce and protect the rights. Informational access shall provide for well-informed patients and healthcare providers. All research fields provide for more equitable access to healthcare and in all aspects further improvement is desirable.
Keywords: access to healthcare; dostop; javno zdravstvo; mandatory health insurance; medical services; medicinal goods; medicinske stvari; obvezno zdravstveno zavarovanje; social security; socialna varnost; zdravstvene storitve; zdravstveno varstvo